Chemical and photochemical degradation of polybrominated diphenyl ethers in liquid systems – A review. (1st January 2016) - Santos, Mónica S.F.; Alves, Arminda; Madeira, Luis M.
Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants which have received a great deal of attention due to their persistence, potential to bioaccumulate and possible toxic effects. PBDEs have been globally detected in humans, wildlife and environment, highlighting the urgency of looking for effective removal technologies to mitigate their spread and accumulation in the environment. Among all environmental compartments, the water has raised particular attention. This paper aims to provide information about the suitability of the main degradation processes investigated to date (photolysis, zerovalent iron and TiO2 photocatalysis) for the degradation of PBDEs in water matrices. The most relevant criteria behind the design of a system for such purpose are discussed in detail for each individual process. The comparative analysis suggests that the oxidative degradation by TiO2 is the most appropriated technology to treat waters contaminated with PBDEs because higher debromination and mineralization degrees are achieved, preventing the formation/accumulation of lower brominated PBDE congeners and promoting the cracking of aromatic cores. Highlights: PBDEs degradation in liquid systems. Photolysis is the most studied technique followed by ZVI and TiO2 photocatalysis. PBDEs 209, 99 and 47 are the most investigated congeners. Oxidation processes lead to higher debromination/mineralization degrees than reductive ones. PBDEs degradation by catalyzed ZVI reduces their estrogenic potencies.